The nurse's role in care for children with autistic spectrum disorder (Research, Society and Development, 2022)
The present study focuses on the role of nurses in caring for children with Autism Spectrum Disorder. This theme consists of a current discussion, between the years 2017 and 2022. The time frame was determined to investigate the limitations found in the literature on nurses in the care of children with ASD. The choice of theme was based on the representation of the nursing professional regarding the diagnosis and treatment of autistic children. Thus, the present research was based on academic studies, characterizing the work as a bibliographic, exploratory and qualitative methodology, whose general objective is to highlight the assistance provided to children with Autism Spectrum Disorder. Regarding the results obtained, it was found that the nurse is the health professional who has more contact with the child. In addition, it can play its role helping the family and the community. However, the literature states that there is a lack of trained nurses. This gap allows us to suggest that it is necessary to create public policies to encourage nurses to train themselves.